Painful Temporomandibular Disorder Is Associated With Migraine in Adolescents: A Case-Control Study - Fernandes, Giovana [UNESP] (2019)
Some types of primary headaches and temporomandibular disorders (TMD) are comorbid in adults and highly prevalent in adolescents. Herein, we investigated the association of painful TMD with specific headache diagnoses (migraine, tension-type headache) and with headache frequency in adolescents. We also explored the association of headache diagnosis with the number of painful sites in the trigeminal area. Painful TMD was assessed using the Research Diagnostic Criteria for TMD. We conducted a case-control study of adolescents from 13 to 15 years old who were recruited among participants in a previous epidemiologic study conducted in Araraquara, SP, Brazil. Headaches were classified according to the second edition of the International Classification for Headache Disorders. Logistic, multinomial logistic and linear regression models were used to test associations. Of 149 individuals, 55.7% presented painful TMD. Adolescents with painful TMD (cases) were more likely to have migraine compared with those without TMD (controls; odds ratio = 3.0, 95% confidence interval = 1.47–6.19, P =.033). Significant differences were not observed for probable tension-type headache (P =.307) or tension-type headache (P =.834). Painful TMD was also associated with an increase in headache frequency (linear-by-linear association = 8.051; P =.005). Only migraine was associated with a greater number of painful sites on palpation in the trigeminal area (P =.001). Migraine and frequency of headache were associated with painful TMD in adolescents. Perspective: Migraine and headache frequency were strongly associated with painful TMD in adolescents, and causality must be determined. For now, the presence of 1 condition should raise suspicion of the other and warrants collaboration between orofacial pain specialists and neurologists.